REVISITING PARIWISATA MADURA; STUDI KEBIJAKAN PEMBANGUNAN KEPARIWISTAAN KABUPATEN SAMPANG - Alfisah Nurhayati (Karsa: Journal of Social and Islamic Culture)
Abstract On the view of potency and opportunity,  Madurese tourism seems an interesting matter.  It posesses a characteristic and exotic natural resources, some has been exploited and some others have not been touched yet. Religious and high work-ethic human resources also characterize the potency and it becomes a promising modality of tourism development. Sampang represents for Madura, since it has been a part of the island that has specific social character. Yet the data show that tourism has not become strategical and inter-sectoral  issue. Nevertheles, inter-sectoral ego is being SKPD interest of policy measurement.  Sampang stakeholders---kyai (Islamic scholar) and public are not invited by the government to discuss the tourism discussion. The formation that combines religious (Islamic) tourism and Madura natural potency   would be the social capital in formulating the tourism development in Sampang. Tourism is not about commercial income but also a matter of social, culture, and religion society. Kata-kata kunci komunitas, budaya, wisata